Computer and website-based interventions to improve common mental health problems in university students: a meta-analysis - Davies, E. Bethan; Morriss, Richard K.; Glazebrook, Cris (2014)
Website-based and computer-delivered interventions could improve common mental health problems experienced by university students, as their help-seeking is limited. This review analysed RCT trials of these interventions to improve depression, anxiety and psychological well-being in university students. Studies aimed to trial computer-delivered/website-based interventions to improve symptoms of depression, anxiety, psychological distress and stress in university students. Seventeen trials of fourteen distinct interventions were identified – nine were CBT-based. Compared to inactive controls, interventions were supported in improving anxiety (SMD-0.56, CI -0.77 - -0.35, P=<.00001); depression (SMD-0.43, CI -0.63 - -0.22, P=<.0001) and stress (SMD-0.73, CI -1.27 - -0.19, P=<.008). In comparison to active controls and comparison interventions, analyses did not support either condition for anxiety or depression (all P=>.05). Website-based and computer-delivered interventions can be effective in improving students’ mental health when compared to inactive controls, but caution is needed when compared to other conditions and methodological issues require consideration.